PEMBINAAN SENI BACA ALQURAN DALAM MENINGKATKAN KUALITAS BELAJAR TILAWAH DI DAYAH MODERN ALFURQAN (Pascasarjana Institut Agama Islam Almuslim Aceh, 2024)
The aim of this research is to determine the development of the art of reading the Koran in improving the quality of learning recitations at Dayah Modern Alfurqan. The development of the art of reading the Koran at Dayah Modern Alfurqan involves two meetings a week and one face-to-face meeting takes an hour and a half. The author feels this is a very effective time, but here there is a problem. This type of research is descriptive qualitative, where primary data is obtained from interviews and observations at Dayah Alfurqan, while secondary data is obtained from related articles and journals. As for the results of the research, extra activities were obtained which not only focused on learning Al-Quran songs but still prioritized the rules of the Koran correctly. The coaching schedule per week consists of two meetings and takes one and a half hours. This training was attended by all students, starting from class I MTs students to class III high school students.